Exergy analysis of vapour compression-absorption two-stage refrigeration cycle. (10th June 2021) - Ozturk, Ilhan Tekin; Cimsit, Canan
In this work, the exergy analysis of vapour compression-absorption two-stage refrigeration cycle has been performed. While NH3 -H2 O has been used as fluid pair in the absorption section, NH3 has been used in the vapour compression section. To improve the performance of the cycle, it is possible to reduce the total damage by focusing on the parts that cause high exergy damage. Therefore, the detailed exergy analysis has been made for different operating conditions (generator temperature, condenser temperature and intermediate pressure) of the cycle. The exergy destruction rates of each component were calculated and compared. As the generator temperature increases, the highest exergy destruction rates are seen in the generator. The generator exergy destruction rates increase with increasing condenser temperature. Also, the performance coefficient ( COPcyclegen ) and the exergy efficiency ( ε ) of the novel cycle have been investigated for different the intermediate pressures. The performance coefficient ( COPcyclegen ) increases as the intermediate pressure increases. Maximum value of the exergy efficiency is obtained at the intermediate pressure of 516.015 kPa. With this cycle, it is possible to refrigerate down by using alternative energy sources. Also, the refrigeration system is environmentally friendly because environmentally safe fluids are used in this cycle.